RVF vector spatial distribution models: probability of presence - Wint, W; Van Bortel, W; Schaffner, F (Wiley, 2020)
EFSA has requested the Vextornet consortium to undertake a series of spatial distribution models for seven potential mosquito vectors of Rift Valley fever virus, namely Aedes albopictus, Aedes caspius, Aedes detritus, Aedes japonicus, Aedes vexans, Culex pipiens and Culex theileri. The modelling used the distribution data held within the VectorNet archive (as at September 2018), updated by literature searches to acquire new records available since 2016. The modelling has been implemented in three phases: (i) data collection, collation and standardisation; (ii) spatial modelling for presence and absence, and the calculation of presence metrics at the country level to be compatible with the MintRisk utilities; and (iii) the spatial modelling of vector abundance, dependent on the data available. This document briefly summaries the results of the data collection, and presence and absence modelling due for delivery in December 2020. Sufficient data were amassed to produce statistically reliable spatial models of the probability of presence of all species except Ae. detritus. The models were implemented at 1 km resolution covering the whole of continental Europe, using standard modelling techniques (Boosted Regression Trees and Random Forest) implemented through the VECMAP software suite. The distribution data for the period 2016 onward will be added to the VectorNet archive when its migration to a new data warehouse within ECDC has been completed. All spatial data in the form of an ARCMAP ‘package’ containing summaries of the vector distribution data collected, and all model outputs have been made available online to Vectornet partners, EFSA and ECDC. This interim report will be followed by a more complete document which also includes the results of the abundance modelling, due in March 2020.